(untitled) (Journal of Education and Development, 2020)
As a result of changing missions, quality assurance in global higher education has ascended to the top of the higher education policy agenda in many nations. In order to hold universities accountable despite limited governmental support, many nations have adopted performance-based university funding strategies. Increasingly citizens and bureaucrats in many countries are asking more frequently what tangible benefits the society is receiving for the revenues being spent on higher education. The marketing, selling and financing of higher education has had both positive and negative effects on the future of global higher education because stakeholders are increasingly asking whether students are learning and whether institutions are providing a quality of service that justifies their cost. How do global higher education institutions develop and initiate techniques and programs to promote quality assurance for teaching and learning? Globalization and accountability create an atmosphere in higher education where knowledge and information are more vastly prized and more highly globalized than are localized economic concerns. Can quality assurance provide the framework for the implementation and development quality higher education in a climate of change and ambiguity?